PERAN KEMANDIRIAN DAN KECERDASAN EMOSIONAL TERHADAP PENYESUAIAN DIRI PADA SISWA ASRAMA TAHUN PERTAMA SMK KESEHATAN BALI MEDIKA DENPASAR (Jurnal Psikologi Udayana, 2016)
Personal Adjustment is a process which includes all the individual behavior and mental response in harmonize needs and demands in which it is derived from the inside of individual as well as from the environment. The ability in personal adjustment is needed to help the individual in facing many changes and demands from the environment. Personal adjustment is needed for first-year students in facing the school’s transition, especially for the students who proceed their education in a boarding school. Personal adjustment is affected by the ability in managing the emotion and mental readiness to solve a problem without a help from others. This research is aimed to explore the role of autonomy and emotional intelligence to the personal adjustment in the first-year boarding students. The subjects were 125 boarding students in grade X of SMK Kesehatan Bali Medika Denpasar. The instrument in the research were personal adjustment scale, autonomy scale and emotional intelligence scale. The results of multiple regression analysis showed the value of R=0,783 (p